Benchmark of lamb quality in U.S. retail and foodservice markets - Hoffman, Travis William, author; Belk, Keith E., advisor; Woerner, Dale R., committee member; Ahola, Jason K., committee member; Pendell, Dustin L., committee member; Holt, Timothy N., committee member (Colorado State University. Libraries, 2015)
Quality is an accumulation of attributes that satisfy customer preferences and expectations. Lamb quality is a moving target that means different things to the supply chain and sheep/lamb industry stakeholders. The objectives of this research were to determine the rank, definition, relative preference, and willingness to pay (WTP) for seven quality attributes and quantify product attributes of lamb at U.S. retail markets. Structured interviews of retail and foodservice respondents were conducted from May 2014 to March 2015 via face-to-face or telephone with lamb/protein purchaser representatives of retail (n = 60), foodservice (n = 45), and purveyor (n = 15) marketing sectors. Shares of preference (relative percentage of preference) in best/worst evaluation for all interviews indicated that eating satisfaction (38.9%) was the most important attribute. Shares of preference for all seven specified quality attributes were statistically different from each other (P < 0.05). Credence attributes of origin (17.2%) and sheep raising practices (13.6%) ranked second and third overall, respectively. Physical product characteristic traits of product appearance/composition (10.5%) and weight/size (8.5%) were ranked fourth and fifth in shares of preference, respectively. Nutrition/wholesomeness (7.1%) ranked sixth and product convenience/form (4.2%) ranked seventh in the overall ranking across all sectors of retailer, foodservice, and purveyor interview respondents. In WTP analyses, origin (25.8%) and sheep raising practices (20.0%) had the greatest likelihood of being a non-negotiable requirement for lamb purchasers. Eating satisfaction was the trait most likely to receive a premium (71.7%) from buyers, and product assurance of eating satisfaction generated the greatest average WTP premium (18.6%). This research indicated, across all sectors, eating satisfaction, defined as lamb flavor/taste, was the most important quality trait to those who purchase lamb. In-store evaluations of retail lamb labels showed that lamb shoulder and loin chops originating from the U.S. garnered the greatest price premiums compared to either New Zealand or Australian lamb (P < 0.05). Lamb was merchandised to American consumers at specialty type stores at an increased price per kg premium than either locally owned or national grocery chains (P < 0.05). Lamb shoulder prices at retail were merchandised with the greatest premium for product of U.S. origin from a specialty store packaged in modified atmosphere packaging and labeled with local (+ $5.42/kg) and natural (+ $5.40/kg) claims (P < 0.05). Lamb loin prices at retail were merchandised with the greatest premium for product of U.S. origin from a specialty store merchandised in a full service case or modified atmosphere packaged and labeled with a source verified and branded (+ $7.21/kg) label claim (P < 0.05). Shoulder and loin chop prices analyzed via hedonic modeling were not different for store location (East, Central, and West) nor USDA process verified Never-Ever 3 claim (P > 0.05). Additionally, this research indicated that lamb loin and rib chops purchased at U.S. retail markets originating from U.S. lamb were the most muscular. Loin eye area of loin chops from U.S. origin were greater (19.55 cm2) than Australian chops (16.77 cm2), and chops from New Zealand (14.52 cm2) were the least muscular (P < 0.05). Also, Australian lamb (0.64 cm) had a trimness advantage of external fat of loin chops compared to lamb originating from either the U.S (0.84 cm) or New Zealand (0.86 cm; P < 0.05). Lamb producers should strive to place a strategic emphasis on quality attributes identified in this research to ensure eating satisfaction and lamb flavor are optimized for American Lamb, and to produce lamb with product authenticity attributes requested by retail and foodservice sectors, and inevitably American lamb consumers. An important application of the research included the development of an American lamb quality mission to: improve the consistency of quality, cutability, and marketability of American lamb with a consumer driven focus. The final phase of this project was a sheep/lamb industry strategy workshop that identified goals to: 1) Address factors contributing to lamb flavor, their impact on consumer satisfaction, and align flavor characteristics with target markets; 2) Improve lamb management to hit market-ready targets for product size, composition, and eating satisfaction while reducing production costs; and 3) Identify and capitalize on market opportunities for American lamb. A continuous improvement mentality is essential to lamb quality management throughout the supply chain in order to maintain (and increase) market share and demand for American lamb.
Keywords: economics; foodservice; lamb; quality; retail